STAT4 targets KISS1 to promote the apoptosis of ovarian granulosa cells - Jiang, Yao (J Ovarian Res, 2020)
BACKGROUND: In mammals, it is known that the estradiol-17β (E2) is mainly synthetized in ovarian granulosa cells (GCs), and the excessive apoptosis of GCs induces the follicular atresia. Many studies have implicated the essential role of KISS1, with the pro-synthetic effect of E2 and the anti-apoptotic effect on GCs, in the mammalian folliculogenesis, and several STAT4 potential binding sites were previously predicted on the promoter of KISS1 in pigs. However, the biological effects of STAT4 on GCs and the molecular regulation between STAT4 and KISS1 remained largely unknown. METHODS: Using the porcine GCs as the cellular model, the overexpression plasmid, small interfering RNA, 5′-deletion and luciferase assay were applied to investigate the molecular mechanisms for STAT4 regulating the expression of KISS1. RESULTS: In this study, the STAT4 negatively regulated the mRNA and protein levels of KISS1 in porcine GCs, and the mRNA level of STAT4 was observed to significantly decrease from immature to mature follicles, which was inversed with that of KISS1. The relative luciferase activity of KISS1 promoter was significantly increased with deletion of the fourth potential binding site (− 305/− 295), and ChIP further confirmed that the STAT4 bound at − 305/− 295 region of KISS1. Besides, the STAT4 significantly regulated the mRNA levels of PDK1, FOXO3 and TSC2 of PI3K signaling pathway to promote the cell apoptosis and the percentage of cells at G0/G1 phase of cell cycle in GCs. Alternatively, the STAT4 significantly decreased the mRNA levels of CYP17, 3B-HSD, 17B-33 HSD, ESR1, and ESR2, as well as the concentration of E2 in GCs. Furthermore, interfering with the expression of STAT4 was observed to significantly stimulate the pro-synthetic effect of E2 and anti-apoptotic effect of KISS1 in GCs. CONCLUSIONS: Collectively, the STAT4 might directly target at − 305/− 295 region of KISS1 to negatively regulate the transcription of KISS1, promote the cell apoptosis via PI3K signaling pathway, suppress the synthesis of E2 through the estrogen signaling pathway in porcine GCs. These proposed works could provide useful insight in further investigations on the molecular functionalities of STAT4 and KISS1 in the folliculogenesis of mammals.